Benthopelagic Deep-Sea Food Webs Along a Latitudinal Gradient in the Scotia Sea (Southern Ocean) - José P. Queirós; Mark Belchier; José Abreu; Paco Bustamante; Martin A. Collins; Ana M. M. Gonçalves; Irene Bermúdez-Gutiérrez; Gabriele Stowasser; Diana Vaz; Philip R. Hollyman; José C. Xavier (Ecosystems, 2025)
Understanding food-web structure is crucial to determine the functioning of ecosystems and sustainably manage resources. The Scotia Sea is an important area for Antarctic krill and toothfish fisheries, and one of the regions most impacted by climate change in the Southern Ocean. Whilst the pelagic Antarctic krill-centric food web has been investigated in reasonable detail, the structure of deep-sea food webs associated with toothfish fisheries remain largely unknown. Utilising stable isotopes and fatty acids as trophic proxies, we studied the deep-sea food-web structure in three locations of the Scotia Sea, from South Georgia (SG) to the South Sandwich Islands (SSI; divided into north and south). Our analyses indicate that all food webs were similar, presenting high trophic redundancy and similar vertical structure. All food webs had five trophic levels, with the 5th and 4th trophic levels mainly constituted of fish and the 3rd trophic level of cephalopods and crustaceans. However, some differences existed with the SG food web presenting larger diversity of producers and the bigeye grenadier Macrourus holotrachys in the highest trophic position, while Patagonian toothfish Dissostichus eleginoides and both Patagonian and Antarctic toothfish D. mawsoni were the top predators at SSI-North and SSI-South, respectively. Compared to coastal and pelagic food webs in the Southern Ocean, our results suggest that deep-sea food webs, including the benthic/demersal components, have a longer food-chain length. This study provides essential knowledge of the ecological variability of Southern Ocean deep-sea food webs while contributing to the management of resources within the SG and SSI Marine Protected Area.